증상 유형별로 분류한 소화불량 환자 62개 증례 관찰 보고 - 하유빈; 신길조; Ha, Yu-bin; Shin, Gil-cho (대한한방내과학회지, 2020)
Objectives: The purpose of this study was to propose a diagnostic method for classifying patients with dyspepsia by symptom type. The correlation between symptom types and X-ray findings was studied in 62 patients with indigestion. Methods: In this study, the complaints and abdominal X-ray findings were collected for 62 patients who visited the outpatient Korean medicine clinic. The medical information related to dyspepsia was grouped for similar patients and classified by symptom type. Results: The patients with dyspepsia were classified into three types according to their medical symptoms: Distention type (N=43, 68.3%), Abdominal Pain type (N=16, 25.5%), and Constipation type (N=12, 19.0%). Intestinal fecal findings (80.6%) on x-rays were noted in most of the cases, followed by intestinal gas pattern findings (14.5%). Conclusion: Classifying patients with dyspepsia by symptom types is an appropriate diagnostic method due to the unclear pathophysiology of indigestion and the difficulty in applying a Korean medical dialectic. Irrespective of the symptom types, the large number of fecal material findings (80.6%) on x-rays means an effect on the interior environment of the body where intestinal feces accumulate easily and decreased gastrointestinal motility in patients with indigestion. This can be correlated with "food accumulation (食積)" as intestinal feces are tangible substances. In addition, gas in the intestine increases visceral sensitivity, causing abdominal distention or pain. The gas pattern findings (14.5%) on x-ray were observed in the "Distention type" and "Abdominal pain type," but not in the "Constipation type."